GEJALA BAHASA SISWA KELAS X DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Ika Agustina Pratiwi; Mulyanto Widodo; Siti Samhati (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2014)
This study is aimed at describing the linguistic phenomena among students at the first year of senior high school in academic year 2013/2014 and the implication toward Indonesian learning. The method is descriptive qualitative. The data collecting technique are observation, interviews, and recordings. Based on data analysis, it was found that there are fourteen linguistic phenomena: (1) afaresis, (2) syncope, (3) apocope, (4) paragoge, (5) the linguistic phenomena of language adaptation, (6) the substitution of prefix, (7) the substitution of simulfix, (8) the substitution of sufix, (9) the removal of phonemes, (10) irregularity, (11) the use of the particle, (12) contraction, (13) acronyms, and (14) abbreviation. The implication in Indonesian learning was using Indonesian appropriately as a tool to get the practical purpose and solve problem in a life and also to do social relationship honestly and politely.Tujuan penelitian ini adalah mendeskripsikan gejala bahasa siswa kelas X SMA tahun pelajaran 2013/2014 dan implikasinya terhadap pembelajaran bahasa Indonesia. Metode penelitian adalah deskriptif kualitatif. Teknik pengumpulan data yaitu teknik pengamatan, wawancara, dan rekaman. Berdasarkan hasil analisis data, ditemukan 14 gejala bahasa, yaitu (1) afaresis, (2) sinkop, (3) apokop, (4) paragog, (5) gejala adaptasi bahasa, (6) subtitusi prefiks, (7) subtitusi simulfiks, (8) subtitusi sufiks, (9) penghilangan fonem, (10) ketidakteraturan, (11) penggunaan partikel, (12) kontraksi, (13) akronim, dan (14) singkatan. Implikasi dalam pembelajaran bahasa Indonesia yaitu menggunakan bahasa Indonesia yang baik dan benar sebagai sarana untuk mencapai tujuan praktis dan menyelesaikan berbagai masalah dalam kehidupan.Kata kunci: gejala bahasa, implikasi pembelajaran, siswa.